The study of electron transfer reactions in a dendrimeric assembly: proper utilization of dendrimer fluorescence. Issue 36 (26th August 2016) - Koley, Somnath; Ghosh, Subhadip
Abstract : Sensing applications of dendrimers: trapping of explosive nitroaromatic compounds within the dendrimer-cage followed by efficient quenching of its fluorescence. Abstract : The PAMAM dendrimer with a cage like structure acts as an excellent electron donor in the presence of an electron deficient molecule. Electron transfer (ET) causes significant quenching of dendrimer fluorescence. Trapping of quencher molecules within the dendrimer cage helps ET to take place through an expeditious route. Utilization of intrinsic fluorescence and sensing applications of dendrimers have been established here.